Case Study : Dherb’s Holdings (M) Sdn. Bhd. / Hani Arissa Halimi - Halimi, Hani Arissa (2021)
As a student in UiTM Kota Bharu, the case study project is part of the study for students. So, for this purpose, I had chosen D’herbs Holdings (M) Sdn. Bhd. as my company research in this project. This case study is focusing on health and beauty products. D’Herbs Holdings (M) Sdn. Bhd. has run for about 11 year started in September 2010 which form by Dato’ Aliff Syukri Kamarzaman which is the founder and Managing Director of the company which located at Petaling Jaya, Selangor. In this case study, I had to identify the issues and problems currently happening towards the company. From the finding, there are four (4) problems were recognized in this case study, which are insufficient stock availability, unattractive packaging, no official website, and an inactive online store. All these problems affected the overall D’Herbs Holdings (M) potential to be the top health and beauty company in Malaysia. All problems faced by D’Herbs Holdings (M) had instigated most of the customers. The customers feel dissatisfied with the company’s performance. Based on findings and discussion, all these problems were identified where all these problems exactly happened against D'Herbs Holdings (M). Although four (4) problems were highlighted, there are two (2) major problem which is insufficient stock availability, and no official website was deliberated in the discussion. The discussion has also included an alternative solution to the problems which includes pros and cons of each of the solution. In addition, I also have analyzed the strength, weaknesses, opportunities, and threats of the company by using SWOT analysis. Based on the observation, this company has a wide and varied range of products, high-quality products, affordable price products, good marketing and also using natural ingredients without preservatives. Last but not least, I also suggest the best solution and recommendation to resolve the problem faced by D’Herbs Holdings (M). There are two (2) recommendation presence suggested which are training the staff, stay ahead of competitors, increase job satisfaction level, and upgrading patty machine (The Hollymatic Super Patty machine). Therefore, all these recommendations are hoping can resolve or reduce to some extent the problems faced by the company.